Diseño de un plan estratégico para la Cooperativa de Ahorro y Crédito Semilla del Progreso del Cantón Saraguro durante el período 2011 - Armijos González, Maritza Paola (2016)
This researchs tems from a need to apply the know ledge acquired in university classrooms and make a propos alto a company to achieve the required development. When this institution analysis detected that lacked a STRATEGIC PLAN, to guide its course, so my thesis topic: DESIGN OF A STRATEGIC PLAN FOR SAVINGS AND CREDIT COOPERATIVE SEED OF PROGRESS from CANTON SARAGURO during the period 2011. The proposed objectives of turned fully, including: Knowing the business philosophy, Making a situational analysis of the environments surrounding the cooperative, establish strategic goals, formulate strategies and design the tactical and operational plan. To carry out the necessary work was secondary sources and primary sources were collected through observation, interviews and surveys, the proposed work was performed with the help of workshops with the participation of the directors, partners and employees. Theme thods used were the deductive, inductive, analytical, statistical and mathematical. In the main results can be said that the Cooperative has strengths and talents of young, partner loyalty, very good rating for their services, is part of the interbank payment system. But it also has weak nesses that must be eliminated as missing jobs, poor positioning, demotivated staff, poor technology. Among the threat sit faces are: Competition, Bad culture of savings, reduced purchasing power, increased unemployment and poverty. And the opportunities they have are: Technology, remittance flows, a large number of suppliers, growth of the productive sectors, the requirement of financial products and services. Tactical and Operational Plan presents the following activities: Minimize the default rate; Acquire technological tools to improve customer service, increase market share through deposits. Providing financial education to the population. Design and implement marketing strategies, communication and attention to customer service, integrate and train employees. To execute the operational plan for 2012 (short-term), managers must take actions that are indicated in each plan and need a budget that totals $ 88,438.08. It is recommended that each year planned indicators compare with the indicators obtained to perform corrective actions. And hire the necessary personnel according to the growth of the cooperative This ensures efficiency in the service.